PENDIDIKAN POLITIK INKLUSIF SEBAGAI STRATEGI PENINGKATAN LITERASI DEMOKRASI PADA KOMUNITAS NELAYAN - Muh Fichriyadi Hastira; Sry Reski Mulka; M. Aviv Adhitya Putra Pratama; Dea Rizky Amalia; Rahmat Hidayat (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
This community service program was implemented in Rawa Makmur Subdistrict, Samarinda City, with the aim of enhancing political literacy and democratic participation among fishing communities. The activities were designed using a participatory approach, employing interactive lectures, group discussions, and evaluation through pre-test and post-test assessments. A total of 50 participants took part in the program, representing five fishermen groups. The training materials focused on democratic principles, the functions of elections, and forms of citizen political participation. Pre-test results indicated that although the majority of participants had a basic understanding of democracy, inaccuracies were still found in responses related to the requirements for valid elections and the functions of political participation. Following the training, post-test results demonstrated a significant improvement, with all participants understanding the core principles of democracy and the functions of elections, and 98% of participants correctly answering questions regarding democratic characteristics, electoral periods, and the legal requirements of elections. These findings indicate that inclusive political education using a participatory approach is effective in improving political literacy among coastal communities. The program not only strengthened procedural understanding of democracy but also fostered substantive awareness of the importance of citizen engagement in local-level public decision-making.